2004
DOI: 10.1111/j.1540-6040.2005.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Divided over Diversity: Political Discourse in a Chicago Neighborhood

Abstract: In a Chicago neighborhood made up of different racial and economic groups, nearly everyone claims to value diversity. Yet, this powerful and plastic symbol can influence political activity in opposite directions. An ethnographic study of the neighborhood shows how three different groups—white real estate professionals and politicians, white progressive organizers, and black low‐income housing advocates—deploy diversity. It presents three key findings: (1) mixed‐income housing often becomes a proxy for diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 29 publications
(32 reference statements)
0
94
0
Order By: Relevance
“…However, other studies have suggested that the share of minorities that gentrifiers favor for such diversity is limited (Bader 2011; Berrey 2005; Gale 1979; Hwang and Sampson 2014). Survey evidence on the residential preferences of the general population has found that people prefer integrated neighborhoods but favor white neighbors the most, black neighbors the least, and Asian over Hispanic neighbors in the middle (Charles 2003).…”
Section: How Immigration Influenced Early Gentrificationmentioning
confidence: 99%
“…However, other studies have suggested that the share of minorities that gentrifiers favor for such diversity is limited (Bader 2011; Berrey 2005; Gale 1979; Hwang and Sampson 2014). Survey evidence on the residential preferences of the general population has found that people prefer integrated neighborhoods but favor white neighbors the most, black neighbors the least, and Asian over Hispanic neighbors in the middle (Charles 2003).…”
Section: How Immigration Influenced Early Gentrificationmentioning
confidence: 99%
“…Taken as a whole, we see that although diversity as an abstract value is widely embraced, the appeal of integration and diversity is not in its ability to transform the system of racial inequality that persists in the United States (e.g., Berrey 2005;Downey 1999). In the kind of diversity captured by the ideal neighborhood results, and the explanations provided especially by Whites for why it is desirable, there are similarities and reflections of what Bell and Hartmann (2007) referred to as "Happy Talk."…”
Section: Resultsmentioning
confidence: 96%
“…According to the relationship between these variables, four factors that appear of gentrification characteristic is revitalizing the area, social changes, changes in population, and segregation or segmentation. These characteristic factors affirm the synthesis of the theory of Smith (1979), Bourne (1982), Berrey (2005), and Warde (in Smith, 2002) as described in Table 1.…”
Section: Gentrification Characteristics In Tembalang As Semarang's Sumentioning
confidence: 87%